2015
DOI: 10.1111/bjd.13721
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA expression precede changes in micro RNA expression in lesional psoriatic skin during treatment with adalimumab

Abstract: This study demonstrates that the changes seen in the cytokine expression levels after 4 days of treatment with adalimumab are not facilitated by early changes in miRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
1
35
1
1
Order By: Relevance
“…Thus, TNF is essential for the pathogenesis of psoriasis . Anti‐TNF‐α biological drug etanercept significantly suppressed a panel of 38 miRNA and validated serum levels of miR‐106b, miR‐26b, miR‐142‐3p, miR‐223 and miR‐126 were significantly downregulated, while adalimumab could increase miR‐23b indicating changes in the miRNA level may reflect a previously unknown effect of anti‐TNF‐α therapy and may become a biomarker monitoring therapeutic effects. Along with this study, other miRNAs were tested as biomarkers reflecting the therapy responses in cancers.…”
Section: Mirna As Potential Biomarkers In Psoriasismentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, TNF is essential for the pathogenesis of psoriasis . Anti‐TNF‐α biological drug etanercept significantly suppressed a panel of 38 miRNA and validated serum levels of miR‐106b, miR‐26b, miR‐142‐3p, miR‐223 and miR‐126 were significantly downregulated, while adalimumab could increase miR‐23b indicating changes in the miRNA level may reflect a previously unknown effect of anti‐TNF‐α therapy and may become a biomarker monitoring therapeutic effects. Along with this study, other miRNAs were tested as biomarkers reflecting the therapy responses in cancers.…”
Section: Mirna As Potential Biomarkers In Psoriasismentioning
confidence: 89%
“…[13,58,95] Thus,TNFisessentialforthe pathogenesis of psoriasis. [58] Anti-TNFα biological drug etanercept significantlysuppressedapanelof38miRNAandvalidatedserumlevels of miR-106b, miR-26b, miR-142-3p, miR-223 and miR-126 were significantlydownregulated, [85] while adalimumab could increase miR-23b [96] indicatingchangesinthemiRNAlevelmayreflectapreviously unknowneffectofanti-TNFα therapy and may become a biomarker…”
Section: Mirna Levels Monitor Therapeutic Effectsmentioning
confidence: 99%
“…Changes of miRNA expression profile were also observed with adalimumab. Researchers highlighted the possibility for potential introduction of miRNA as molecular markers for treatment efficacy, and the time after which it would be reasonable to examine their concentrations [63]. Finally, miR-320a-c and miR-9, which is credited with a key role in differentiating T-lymphocytes to Th 17 phenotype, are promising molecules that could be used as markers of response to treatment involving anti-IL-12/23 and anti-IL-17 [64].…”
Section: Markersmentioning
confidence: 99%
“…In this issue of the BJD , Raaby and colleagues report on their findings regarding miRNA levels in psoriatic skin during anti‐tumour necrosis factor (TNF) therapy . The authors took punch biopsies from patients with psoriasis before and during treatment with adalimumab and analysed the miRNA levels in lesional and nonlesional skin samples.…”
mentioning
confidence: 99%
“…They found that some miRNAs decreased in levels, but only looked after 12 weeks . Evidently, it is tempting to use the dynamics of miRNAs as biological tools to stratify patients, but the findings of Raaby et al . and Pivarcsi et al .…”
mentioning
confidence: 99%